ANALISA LAPORAN KEUANGAN CV. RASYASSA GRAHA TEKNIK PALEMBANG - Haikal, Haikal (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
Conducting an interpretation or analysis of a company's financial statements will be very beneficial for internal and external parties to be able to know the financial situation and development of the company concerned. then the weaknesses and the results that have been considered good enough can be known, so that efforts to improve company performance in the future can be done more effectively. The analysis is done by using several Financial Ratios including Liquidity Ratio, Activity Ratio, and Profitability Ratio. The results of this study show that the financial condition of CV. Rassaassa Graha Teknik is in good and stable condition.